2023
DOI: 10.1177/1357633x231174488
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a home-based telesurveillance program in reducing hospital readmissions in older patients with chronic disease: The eCOBAHLT randomized controlled trial

Abstract: Introduction Given that chronic, long-term conditions are increasingly common in older patients, the impact of telesurveillance program on clinical outcomes is uncertain. This study aimed to evaluate the feasibility and effectiveness of a 12-month remote monitoring program in preventing rehospitalizations in older patients with two or more chronic diseases returning home after hospitalization. Methods We conducted a multicenter randomized controlled trial in two parallel groups to evaluate the remote monitorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Regarding medical factors, Tchalla (2023) implemented a remote monitoring program for 12 months for older patients with chronic diseases. The rehospitalization rate of the intervention group was 40.4% (108 people), and that of the control group was 48.7% (130 people), which showed a significant difference, suggesting the effectiveness of remote monitoring [26].…”
Section: Narrative Synthesismentioning
confidence: 89%
See 2 more Smart Citations
“…Regarding medical factors, Tchalla (2023) implemented a remote monitoring program for 12 months for older patients with chronic diseases. The rehospitalization rate of the intervention group was 40.4% (108 people), and that of the control group was 48.7% (130 people), which showed a significant difference, suggesting the effectiveness of remote monitoring [26].…”
Section: Narrative Synthesismentioning
confidence: 89%
“…Regarding the general characteristics of the literature, they are randomized controlled trial studies; nine articles were found that were conducted in a single country (one each in France, Canada, the Netherlands, Italy, China, and Hong Kong, and three in the United States) [25][26][27][28][29][30][31][32][33], while two were multinational studies (one in the Netherlands, Finland, and France, and one in Spain, the United Kingdom, Slovenia, Estonia, and Sweden) [34,35]. The mean age of participants was 72.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation